The Contribution of the α and β Chains to the Kinetics of Oxygen Binding to and Dissociation from Hemoglobin - Gibson, Quentin H. (1973)
A new type of experiment in which hemoglobin is exposed briefly to oxygen has shown that the half-time of dissociation of oxygen from some partly oxygenated intermediates is about 1 msec at 20° and 10 msec at 2°. The rapid dissociation occurs selectively from one type of chain, provisionally identified as the β-chain. Chains that show the rapid rate of dissociation of oxygen also bind rapidly. It follows that the kinetic equivalent of the Adair equation and the Monod-Wyman-Changeux model are quite unsuited to represent the kinetics of the oxygen-hemoglobin reaction. The reaction of oxygen with hemoglobin closely resembles that of the alkyl isocyanides and differs radically from that of carbon monoxide.